2019
DOI: 10.4018/978-1-5225-5282-6.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disorders Progression

Abstract: Neurodegenerative disorders (NDs) are a diverse group of disorders characterized by selective and progressive loss of neural systems that cause dysfunction of the central nervous system (CNS). The examples of NDs include Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), Parkinson's disease (PD), and Huntington's disease (HD). The aggregated proteins block or disrupt the normal proteosomal turnover, autophagy, and become abnormally modified with time, generating toxicity via pathways thereby result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 129 publications
0
5
0
2
Order By: Relevance
“…UXT serves as a cofactor which regulates gene transcription, and it also plays an essential role in concert with the corepressor URI1 to regulate androgen receptor AR-mediated transcription [46]. UXT has previously been found suitable as a reference gene for cells and tissues of some ruminants, including taurine cattle, zebu, riverine buffalo, and goat [47][48][49]. Recent studies showed that UXT was also selected as a suitable reference gene in yak.…”
Section: Discussionmentioning
confidence: 99%
“…UXT serves as a cofactor which regulates gene transcription, and it also plays an essential role in concert with the corepressor URI1 to regulate androgen receptor AR-mediated transcription [46]. UXT has previously been found suitable as a reference gene for cells and tissues of some ruminants, including taurine cattle, zebu, riverine buffalo, and goat [47][48][49]. Recent studies showed that UXT was also selected as a suitable reference gene in yak.…”
Section: Discussionmentioning
confidence: 99%
“…Among the privileged heterocyclic scaffolds, [1,5]benzothiazepines and fused [1,5]benzothiazepines were on the scope of chemists efforts for several years. [ 1,2 ] These compounds have been described as Calcium channel blockers, [ 3–6 ] hypotensive, [ 7–10 ] drugs of liver diseases, [ 11,12 ] antidepressants, [ 13–15 ] anticholinesterase inhibitors, [ 16–17 ] anticancer, [ 18–23 ] diuretics, [ 24 ] antimicrobials, [ 25–38 ] anti HIV, [ 39–41 ] and antituberculosis [ 42,43 ] agents. The useful procedures for the preparation of 1,5‐benzothiazepines are mainly based on the condensation of 2‐aminobenzenethiol with α,β‐unsaturated ketones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dihydro 1,5‐benzothiazepines have turned out to be fascinating pharmacophores as many derivatives exhibit a plethora of activities like antimicrobial , anti‐HIV , anticancer , antifeedant , antiulcer , anti‐inflammatory , anticonvulsant , and antiplatelet aggregation activities. The pharmaceutical prominence of 1,5‐benzothiazepines has encouraged the researchers all over the world, and many reviews have been documented in the literature, which compiled various aspects related to their synthetic advances and biological importance. Consequently, several synthetic protocols have been developed to access this biodynamic skeleton .…”
Section: Introductionmentioning
confidence: 99%